(untitled) (Baghdad Science Journal, 2024)
Rivers became supersaturated with carbon dioxide (CO2), so they play an essential role in the global carbon budgets. To increase our understanding of the source of CO2 availability in rivers, we studied the role of climate-changed drivers of CO2 availability, which are ‘‘dissolved organic carbon (DOC), and warming’’. We sampled 45 locations of 3 parts within the Tigris River in Baghdad during autumn and winter. The results showed that all the studied variables (water temperature, pH, DOC, CO2) changed over time. The variations in CO2 availability are associated with changes in DOC concentration, not with water temperature. Overall, our results suggest that elevated CO2 in rivers could result from increased DOC inputs. Therefore, we can conclude that increased DOC concentration in rivers was required for microbial respiration and photo-mineralization, which are the primary sources of CO2 in river ecosystems.